ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN PADA RUMAH MAKAN TUNGGAL RASA DI SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Arief, Mohammad Yahya; Permatasari, Ayu Dian; Fandiyanto, Randika (Relawan Jurnal Indonesia, 2023)
Marketing is an essential part of the sustainability and development of a company. Therefore, Rumah Makan Tunggal Rasa must be able to choose the right marketing strategy to develop the business and maintain business stability because it is one of the keys to business success. This study analyses and tests store image and product quality's effect on customer loyalty at Rumah Makan Tunggal Rasa, with consumer satisfaction as an intervening variable. Sampling techniques are determined by probability sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that the store image has a significant effect on customer satisfaction, consumer quality has a significant effect on purchase satisfaction, and customer satisfaction has a significant impact on consumer loyalty. The results of the indirect effect hypothesis test show that the variable store image on customer loyalty through customer satisfaction has a significant positive effect, and product quality on customer loyalty through customer satisfaction has a significant positive impact.